Local and regional determinants of vascular epiphytes mortality in the Andean mountains of Colombia (2015)
Abstract: In this study we present the first census of mortality of vascular epiphyte communities carried out at large-scale in mountains of the Andes. Our goal was to identify the main modes of death and the determinants variables on epiphytes mortality. During one year, we went behind the fate of 4,247 epiphytes in 10 forests (116 host trees) located from 60 to 2900 m a.s.l. Our results suggested that the survival of epiphytes is limited primarily by the instability of substrate constituting a possible risk of extinction for those species with slow life cycles because of the impossibility to colonize new substrates quickly. The role of ET in the probability of death of the epiphytes indicated both the direct (limitation of the metabolism) and indirect impact (increasing the mechanical mortality) that climate change could have on the vascular epiphytes dynamics. The influence of local determinants clarified the effect of the microclimate in the dynamics of this non-tree growth component of the forest.